Developing soft skills of Gen Z accountants in the open innovation era: The roles of absorptive capability and self-learning capability - Pattama Buayai; Jintanee Ru-Zhue; Prasit Rungruang; Berto Usman; Somnuk Aujirapongpan (Journal of Open Innovation: Technology, Market and Complexity)
This study examines the impact of absorptive capability and self-learning capability on the development of soft skills among generation Z accountants in Thailand within the open innovation era. Using a quantitative approach, data were collected from 510 accountants with at least one year of work experience across various regions. The findings confirm that absorptive capability significantly enhances both self-learning capability and soft skills, with self-learning capability also playing a key mediating role in this relationship. Notably, capability and skill levels vary across regions, experience levels, and organizational types, with accountants in urban and corporate settings demonstrating stronger competencies. These results emphasize the need for revised accounting curricula and targeted educational activities to strengthen absorptive and self-learning capabilities while addressing regional disparities in skill development. The findings have important implications for accounting education and professional training, specifically: (1) integrating experiential learning methods that enhance knowledge absorption, (2) incorporating self-directed learning components that foster continuous skill development, (3) designing region-specific training programs to address geographical competency gaps, and (4) developing digital literacy frameworks that prepare new-generation accountants to navigate the technological challenges of the open innovation era.The findings have important implications for accounting education and professional training, ensuring that new-generation accountants are well-equipped to navigate the challenges of the open innovation era.